An Organic Luminescent Molecule: What Will Happen When the "Butterflies" Come Together?. (5th December 2013) - Zhang, Jibo; Xu, Bin; Chen, Jinlong; Ma, Suqian; Dong, Yujie; Wang, Lijuan; Li, Bao; Ye, Ling; Tian, Wenjing
<x xml:space="preserve">Abstract</x> Cross dipole stacking based on a novel fluorescent molecule, 9, 10‐bis (2, 2‐diphenylvinyl) anthracene (BDPVA), is presented. The butterfly‐like structure of BDPVA is the key feature to form the unique aggregation structure and such a stacking mode is highly beneficial for fluorescence emission, resulting in high‐performance amplified spontaneous emission and electroluminescence of BDPVA. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>